ANALISIS MANFAAT TEKNOLOGI INFORMASI DALAM PENGEMBANGAN KELOMPOK USAHA BERSAMA (Studi Analisis Semiotika terhadap UMKM ICSB Kabupaten Karanganyar) - Jaelani Jaelani; Hidup Marsudi (Riset Manajemen dan Akuntansi, 2020)
UMKM have strategic position in the National economic of employment and contribute in the National income. UMKM development and empowerment must reintegrated, systematic and sustainable. Empowerment actors business group includes: information and coordination, capacity building, access to resources and others to increase the business in the end can increase operating income. The application of information technology can improve communication between businesses and related parties that allows the efficiency of good time and cost in developing and empower business group.